STRATEGI UNITED NATION POPULATION FUND (UNFPA) DALAM MENANGANI PERMASALAHAN KEHAMILAN REMAJA DI SIERRA LEONE TAHUN 2018-2022 - Salsabila, Nada; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to analyze the strategies implemented by UNFPA in 2018-2022 in overcoming the problem of teenage pregnancy in Sierra Leone in order to achieve a reduction in fertility rates at the age of 19-15 years. Sierra Leone is one of the countries in West Africa that has the highest teenage pregnancy rate in the world. The problem of teenage pregnancy in Sierra Leone is largely caused by poverty, low education and minimal access to contraception. This research uses qualitative methods with data collection techniques through books, journals and documents originating from official websites. This research uses a pluralism perspective and international organization theory. The results of this research show that UNFPA has issued strategies, namely ensuring the provision of contraceptives, empowering teenagers and adding comprehensive sexuality education to the curriculum, and ending dangerous practices. In this case, UNFPA shows a decrease in the fertility rate at the age of 15-19 years, namely 98/1000 in 2022. Keywords: UNFPA, Teenage Pregnancy, Sierra Leone